(untitled) (Research, Society and Development, 2025)
The present study aimed to expose the characteristics of the laboratory environment in which daily activities are carried out, ranging from chemical laboratories to biological laboratories. Biosafety involves the assessment of occupational risks, the adoption of Good Laboratory Practices (GLPs), the qualification of personnel, and the provision of adequate physical infrastructure. The prevention of accidents, often associated with human error or educational deficiencies, requires knowledge of risk factors and the correct use of Personal Protective Equipment (PPE) and Collective Protective Equipment (CPE). The research employed a quantitative approach, using questionnaires administered to 148 students and healthcare professionals in the Vale do Paraíba region, São Paulo, Brazil. The data focused on biosafety knowledge, the presence of manuals and Standard Operating Procedures (SOPs), and the occurrence of laboratory accidents. It was observed that most students were unaware of the existence of SOPs or biosafety manuals in their laboratories, unlike professionals, who demonstrated greater familiarity. Reported accidents included cuts, needlestick injuries, burns, exposure to chemical agents, and inhalation of volatile substances. Post-accident responses ranged from basic first aid to specialized medical care. Lab coats were the most commonly used PPE, whereas gloves, safety goggles, and masks were frequently neglected. The findings revealed significant gaps in biosafety knowledge and practice, highlighting the need for regular training programs, the dissemination of clear and accessible SOPs, and the promotion of a safety culture based on prevention and collective responsibility.